The return to university after fieldwork: toward disrupting practice-theory challenges identified by mathematics teacher educators - Bjerke, Annette Hessen; Nolan, Kathleen (Frontiers in Education, 2023)
In this paper, we present on a research study that was framed in disruptive pedagogy (DP) to examine the post-field context of mathematics teacher educators’ (MTEs’) practices. We open by referring to common challenges discussed in the literature related to theory-practice transitions of prospective teachers (PTs) as they move from university courses to their field placement. After reviewing these challenges, we then shift our focus toward understanding what MTEs see as challenges in the post-field context of teacher education programs; that is, what practice-theory challenges are identified by MTEs as PTs make the transition from field back to university. Briefly, our thematic analysis suggests that, in the post-field context of teacher education programs, MTEs are challenged by organisational issues and institutional structures; by PTs’ return to the university armed with superficial placement stories and unexamined indicators of ‘good mathematics teaching’; and by the significant emphasis PTs place on mentor voices and ways of teaching, often including unfavourable views on the value of reform teaching. Simply put, MTEs expressed being challenged by PTs’ scepticism, resistance, and lack of conviction toward the role of the university. Additionally, MTEs reported being challenged by their own feelings of resignation that our analysis suggests stems from a growing list of challenges which can result in some MTEs stepping down and settling on a pragmatic approach to their post-field mathematics teaching. To close, implications for MTEs are discussed by pointing specifically to the potential of DP for unpacking practice-theory transitions and in considering the creation of a post-field third space.